MANAJEMEN PEMELIHARAAN FASILITAS DALAM PENGELOLAAN GEDUNG - Labombang, Mastura (MEKTEK, 2008)
Maintenance frequently considered not urgently compared than construction, so the maintenance aspect is not be taken care. If the maintenance not doing, it will cause the economics value and physical value will be descending.The complex problems to maintenance the facility of building needs an examination toward maintenance management aspects. This research evaluates The Facility Maintenance Management in maintaining Building.